A dynamic-static coupling topology optimization method based on hybrid cellular automata. (April 2023) - Zhang, Xiaopeng; Wang, Dengfeng; Huang, Bingtong; Wang, Shuang; Zhang, Zifeng; Li, Shenhua; Xie, Chong; Kong, Dewen
Abstract: To improve the ability of the structure to resist static load (SL) and random vibration load (RVL) and prolong the fatigue life, a random vibration topology optimization method (RVTOM) and dynamic-static coupling topology optimization method (DSTOM) are proposed. RVTOM can directly use RVL for topology optimization, avoiding the huge workload caused by gradient information calculation. DSTOM combines the analytic hierarchy process (AHP) and hybrid cellular automata (HCA), and comprehensively considers SL and RVL in topology optimization. The cantilever beam example shows that the SL topology is challenging to resist random vibration load, and the equivalent load cannot replace the RVL for structural topology. Under random vibration excitation, the fatigue life of RVTOM and DSTOM models increased by 32.98% and 24.35%. The control arm example shows that both models have obtained infinite life. The RVTOM model is reasonable, and the load path obtained enhances the ability of the structure to resist random vibration loads and prolongs the fatigue life. DSTOM model can form a load path to fight SL and RVL effectively.